The “Alzheimer Village”: Assessment of Alzheimer's disease representations in the general population: A cross sectional phone survey - Marion Pech; Céline Meillon; Manon Marquet; Jean‐François Dartigues; Hélène Amieva (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction In most countries, the societal view of Alzheimer's disease (AD) is very negative. The initiatives that are part of the so‐called “dementia‐friendly approach” aim not only at promoting well‐being and dignity of persons suffering from AD but also improving the way they are regarded and their inclusion in society. Unfortunately, scarce research has been conducted to assess whether such goals can be achieved. In France, the experimental Alzheimer Village in Dax is designed as a dementia‐friendly community. Due to the recent opening (2020) and the strong local media coverage of this project, a survey has been designed to determine whether the representations of AD have been impacted by such a project. Methods The survey was conducted before and after the opening of the Alzheimer Village in the city of Dax (hosting the village) and surrounding areas, and in a control city with similar socio‐demographics. The analyses intend to compare different dimensions of the representations and attitudes toward AD in the general population. Results A total of 423 persons living in the Alzheimer Village city (37.4% were men) and 415 persons living in the control city (40.2% were men) were interviewed, resulting in 838 complete questionnaires. The main results report significantly lower rating in the perception of loss of identity (β = −0.57, P = .014) and in the feeling of disgust for persons with AD (β = −0.61, P = .008) in the city hosting the village after the opening of the Alzheimer Village. No significant changes were seen in the control city sample. Discussion While societal representations of AD are very robust and difficult to change, this study suggests a modest but significant evolution of representations of AD in the surrounding areas of the Alzheimer Village. Highlights The French Alzheimer Village is one of the very few ones in the world. This is the first study assessing the impact of an Alzheimer Village on disease representations. After the opening of the village, attitudes toward Alzheimer's disease have changed.